Validation of the Youth Quality of Life Instrument for Portuguese Population - Mendes, Sara (2015)
Introduction: Quality of Life (QoL) plays a remarkable role in practice and public health policy. However, research on QoL among children and adolescents is still scarce and it seems crucial to develop and validate assessment tools for measuring health-related QoL. Objectives: The current study aims to analyse the psychometric properties and validate the Portuguese version of the Youth Quality of Life Instrument. In addition, the convergent and divergent validities are examined with related constructs. Methods: Participants were 507 adolescents, with ages between 12 and 19 years old (M = 15.74; SD = 1.62), attending middle and high schools. Together with YQOL-R, participants also filled out the Kidscreen-27 and the Depression Anxiety and Stress Scales (DASS-21). Results: The Portuguese version of YQOL-R showed a four-factor structure (dimensions: Self, Relationships, Environment, General Quality of Life), similar to the original version. This instrument also revealed good internal reliability and adequate temporal stability. YQOL-R showed positive correlations with health-related quality of life and negative associations with depression, anxiety, and stress symptoms. There were significant gender differences regarding quality of life, with boys reporting higher levels of perceived quality of life than girls. Conclusions: Future studies should be conducted to ensure these findings among clinical samples or physical conditions. Nevertheless, this study contributes to the set of available instruments for the assessment of QoL among children and adolescents, suggesting that the YQOL-R may be a useful tool for research and health practices in community samples.